1998
DOI: 10.1017/s002221510014126x
|View full text |Cite
|
Sign up to set email alerts
|

Study of common aerobic flora of human cerumen

Abstract: Cerumen is the product of the secretion of the sebaceous, ceruminous or apocrine glands together with cells exfoliated from the cornified stratum of the epithelium of the external auditory canal (EAC).In the present study we identified and quantified common flora of human cerumen. The mean count obtained was 106 microorganisms per ml of cerumen suspension.In 24 pools of cerumen (33.3 per cent) the isolates were monomicrobial, Staphylococcus epidermidis (12), Corynebacterium spp (10), Staphylococcus aureus (1) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 16 publications
0
19
0
1
Order By: Relevance
“…3 Campos et al found 10 6 microorganisms/ml in the suspension of cerumen. 2 Campos et al attributed this difference to the fact that the study was conducted in the Canary Islands, a subtropical region. They said that another factor that may justify their high count nding is fresh cerumen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Campos et al found 10 6 microorganisms/ml in the suspension of cerumen. 2 Campos et al attributed this difference to the fact that the study was conducted in the Canary Islands, a subtropical region. They said that another factor that may justify their high count nding is fresh cerumen.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] Ceruminous glands are modi ed apocrine sweat glands. There are approximately 1000 to 2000 ceruminous glands in a normally developed EAC.…”
Section: Introductionmentioning
confidence: 99%
“…Among these, Staphylococcus epidermidis, Corynebacterium spp. and Candida albicans seem of major importance, although the microbial spectrum may vary according to climatic conditions and to the length of time the cerumen has remained in the external auditory canal (Campos et al 1998). In this connection, it is of interest that most of the sugars found in the secretions of the ceruminous glands and the sebaceous glands in the pony may be liberated on the skin surface by microbial activities, and then gain the ability to inhibit the adherence of different bacteria and fungi to the epidermis (Meyer et al 2000(Meyer et al , 2001.…”
Section: Discussionmentioning
confidence: 99%
“…[8,9] Absence of cerumen may lead to infection, such that cerumen serves an antimicrobial role by physically protecting the external auditory canal skin, establishing a low pH; thus an inhospitable environment for pathogens and producing antimicrobial compounds such as lysozyme, so that its absence leaves the canal vulnerable to infection.…”
Section: Discussionmentioning
confidence: 99%